Understory Birds Of Gunung Silam, Sabah, Malaysia - Mustapa, Abdul Rahman; Isa, Sait; Mohd Tajuddin, Abdullah (Universiti Malaysia Sarawak, 2011)
An assessment of the understory birds was conducted at Gunung Silam, Sabah, Malaysia. Gunung Silam is located on the eastern end of Segama Highlands, east of Sabah. The site selected for the study was near the telecommunication transmission tower. Twenty black mist nets with four shelves ( 2.5 m x 12 m, 35 mm mesh) were deployed during the study period that made up 1060 net units. A total of 28 birds were caught (including two recaptures) representing 12 species. 62% of the birds were captured in the morning and 32% in the afternoon. Great Argus (Argusianus Argus) calls were heard from three different locations. Owls were spotted three times during the spotlighting exercise.